The Irish Language – a Unique Part of Irish Life and Cultural Revitalisation and Protection - Anna Slatinská (Ksiegarnia Akademicka Publishing, 2017)
The present paper is devoted to the topic of the Irish language and its relation to Irish identity in the modern world, taking into account crucial aspects of the language’s revitalisation and protection. The focus is predominantly on particular ways of achieving the ambitious goal of societal bilingualism in Ireland in the long term. The notion that language and identity are interrelated is the leitmotif of this chapter. Approaching the issue from socio-linguistic and ethnographic perspectives, the revitalisation of the Irish language may trigger the interest of the wider public, assuming that language is an invaluable part of spiritual, nonmaterial culture. Indeed, we consider that the death of the Irish language would be a serious loss not only in the sphere of Ireland’s cultural and national heritage, but also in the wider European sphere.